Catalytic Nucleophilic Fluorination of Secondary and Tertiary Propargylic Electrophiles with a Copper-N-Heterocyclic Carbene Complex - Cheng, Li-Jie; Cordier, Christopher J. (Angewandte Chemie International Edition, 2015)
A catalytic method for the nucleophilic fluorination of propargylic electrophiles is described. Our protocol involves the use of a Cu(NHC) complex as the catalyst and is suitable for the preparation of secondary and tertiary propargylic fluorides without the formation of isomeric fluoroallenes. Preliminary mechanistic investigations suggest that fluorination proceeds via copper acetylides and that cationic species are involved. A carbene can: A Cu(NHC)‐catalyzed nucleophilic fluorination of propargylic electrophiles was found to be suitable for the synthesis of secondary and tertiary propargylic fluorides without the formation of isomeric fluoroallenes (see scheme; NHC=N‐heterocyclic carbene, Ms=methanesulfonyl, Ts=p‐toluenesulfonyl). Preliminary mechanistic investigations suggest that fluorination proceeds via copper acetylides and involves cationic species.